Open-Ended Question Solving Ability Based on Mathematical Creative Thinking Disposition - Yandi, Yandi Heryandi; Aniti (Educational Insights, 2024)
The purpose of this study is to determine the level of mathematical thinking and find out the problem solving skills on open questions based on the differences in mathematical creative thinking dispositions. This study used descriptive qualitative analysis to obtain a clear insight of the facts and phenomena studied. The students of class XI IPA MAN 1 Cirebon as subjects of the study.The researcher found that problem solving skill divided three level: 9% of students have a high level of mathematical problem solving skill, 82% of students have middle level of mathematical problem solving skill, and 9% of students have a low level of mathematical problem solving skill. Students with high level of mathematical creative thinking disposition understood the problem well, makes and carrying a settlement plan, and re-examining the process and results. A middle level of mathematical creative thinking understood the problem well, but mostly they are less able to make and implement a complete plan, and do not fully examining the process and results. Students with the low disposition level of mathematical creative thinking, mostly they understood the problem. Whereas they cannot make and carred out the plan correctly, and they do not re-examining the process and results.